Proposta de um método de participação da produção utilizando o desenvolvimento enxuto de produto - Campos, Telmo Ribeiro de (2008)
Lean manufacturing tools are well known and implemented to eliminate waste and improve materials flow throughout a production process. These lean principles are now studied and applied to product development process (PDP), aligned to the company s needs to develop and launch new products with lower cost and increased speed. Therefore, the objective of the present dissertation is to propose a production preparation procedure, that emphasizes: the significance of the manufacturing team s participation from project inception by sharing its experience, requirements and constraints; the vision of operational value stream delivery as a result of PDP and value creation related to customer and other stakeholders perception. To validate this proposal, a comparative application took place using a previous project from the company that was studied. Procedure comprehensiveness was assessed by questionnaire sent to professionals from other divisions, in addition to the division team. It was concluded that the proposed procedure is: feasible, updated and applicable; capable of contributing to waste, rework and project time reduction and helpful for sharing manufacturing lean concepts knowledge and expertise with other team members and product development stakeholders.